The Basque Nation On-Screen - Cinema, Nationalism and Political Violence - Tal, Tzvi (Imagofagia, 2021)
Sobre De Pablo, Santiago. The Basque Nation On-Screen - Cinema, Nationalism and Political Violence. Reno: Centre for Basque Studies, University of Nevada, 2012, 471 pp., ISBN: 9781935709237 Palabras clave: reseña, De Pablo, Santiago, The Basque Nation On-Screen - Cinema, Nationalism and Political Violence